Rational design of asymmetric supercapacitors via a hierarchical core–shell nanocomposite cathode and biochar anode. Issue 72 (20th December 2019) - Fan, Meiqing; Zeng, Xu; Yang, Xiaodong; Zhang, Xin; Ren, Bo
Abstract : Hierarchical MnO2 nanosheets standing on hollow NiO microspheres have been designed by a facile hydrothermal process. Furthermore, asymmetric supercapacitors via core/shell NiO/MnO2 cathode and biochar anode were assembled. Abstract : Hierarchical MnO2 nanosheets attached on hollow NiO microspheres have been designed by a facile hydrothermal process. The core–shell structure is achieved by decorating an MnO2 nanosheet shell on a hollow NiO sphere core. The highly hollow and porous structure exhibits a high surface area, shortened ion diffusion length, outstanding electrochemical properties (558 F g −1 at a current density of 5 mA cm −2 ), and excellent cycling stability (83% retention after 5000 cycles). To further evaluate the NiO/MnO2 core–shell composite electrode for real applications, three asymmetric supercapacitors (NiO/MnO2 //pomelo peel (PPC), NiO/MnO2 //buckwheat hull (BHC), and NiO/MnO2 //activated carbon (AC)) are assembled. The results demonstrated that NiO/MnO2 //BHC delivered a substantial energy density (20.37 W h kg −1 at a power density of 133.3 W kg −1 ) and high cycling stability (88% retention after 5000 cycles) within a broad operating potential window of 1.6 V.